Innovation in publishing: Why we need systems for the review and curation of preprints - Hutton, Fiona (Septentrio Conference Series, 2023)
Watch VIDEO.The growing number of papers published openly as preprints on bioRxiv and medRxiv during recent years has highlighted how preprints can accelerate and democratise access to research. However, it has also shown the need for systems of review that help readers easily assess the quality of new findings.A number of groups are now working to openly peer-review preprints, making them more useful for authors, readers, the broader research community and the general public. Some of these models are also taking advantage of the open nature of preprints to enable researchers from groups traditionally underrepresented in science to participate in public review, sharing their expertise and perspectives with authors, readers and others who engage with preprints. These groups include, for example: ASAPbio–SciELO Preprints crowd review, Biophysics Colab, the Novel Coronavirus Research Compendium, and eLife, which officially launched a new model for publishing in January 2023.eLife’s new model eliminates accept/reject decisions after peer review and focuses instead on providing quality public reviews and assessments. The output is a Reviewed Preprint, which combines the immediacy and openness of preprints with the scrutiny of peer review by experts. This model feeds into eLife’s overarching ‘publish, review, curate’ mission that puts preprints first.In this presentation, we will highlight the work of eLife in reviewing and curating preprints, and discuss why transforming preprints into reviewed preprints will have significant benefits for scientists and science more broadly.
Keywords: Preprints; Peer review; Public review; Open science